Long-Term Cognitive Decline After Stroke: An Individual Participant Data Meta-Analysis. Issue 4 (15th November 2021) - Lo, Jessica W.; Crawford, John D.; Desmond, David W.; Bae, Hee-Joon; Lim, Jae-Sung; Godefroy, Olivier; Roussel, Martine; Kang, Yeonwook; Jahng, Seungmin; Köhler, Sebastian; Staals, Julie; Verhey, Frans; et al.
Abstract : Background: Poststroke cognitive impairment is common, but the trajectory and magnitude of cognitive decline after stroke is unclear. We examined the course and determinants of cognitive change after stroke using individual participant data from the Stroke and Cognition Consortium. Methods: Nine longitudinal hospital-based cohorts from 7 countries were included. Neuropsychological test scores and normative data were used to calculate standardized scores for global cognition and 5 cognitive domains. One-step individual participant data meta-analysis was used to examine the rate of change in cognitive function and risk factors for cognitive decline after stroke. Stroke-free controls were included to examine rate differences. Based on the literature and our own data that showed short-term improvement in cognitive function after stroke, key analyses were restricted to the period beginning 1-year poststroke to focus on its long-term effects. Results: A total of 1488 patients (mean age, 66.3 years; SD, 11.1; 98% ischemic stroke) were followed for a median of 2.68 years (25th–75th percentile: 1.21–4.14 years). After an initial period of improvement through up to 1-year poststroke, decline was seen in global cognition and all domains except executive function after adjusting for age, sex, education, vascular risk factors, and stroke characteristics (−0.053 SD/year [95% CI, −0.073 to −0.033]; P <0.001 for global cognition). Recurrent stroke and older age were associated with faster decline. Decline was significantly faster in patients with stroke compared with controls (difference=−0.078 SD/year [95% CI, −0.11 to −0.045]; P <0.001 for global cognition in a subgroup analysis). Conclusions: Patients with stroke experience cognitive decline that is faster than that of stroke-free controls from 1 to 3 years after onset. An increased rate of decline is associated with older age and recurrent stroke.